From Vision to Practice: Transformational Leadership in Aligning Digital Adaptation with Islamic Values in Indonesian Sharia Hotels - Rivai, Andi Muhammad; Suyuti, Muh. Rizal; Baharuddin, Aris; Salam, Rudi; Munna, Afzal Sayed (Sekolah Tinggi Agama islam Negeri Majene, 2025)
Sharia-compliant hotels in Indonesia are increasingly challenged to maintain religious integrity while embracing digital transformation. This study investigates how transformational leadership supports the integration of digital technologies in accordance with Islamic principles, recognising that although leadership is not explicitly regulated, the operational guidelines provide a normative framework that leaders are expected to interpret and implement in practice. A qualitative observational approach was employed. Data were collected from nine Sharia hotels in Makassar and Malang. The data were analysed using a six-phase thematic analysis framework, which enabled the systematic identification, coding, and interpretation of patterns across the entire dataset. The findings reveal that transformational leadership, which is characterised by visionary direction, motivational influence, and supportive engagement, is crucial in aligning technological adaptation with Sharia values. Hotels with stronger leadership adherence to Islamic ethics were more adherent in implementing digital tools that uphold modesty, halal standards, and moral conduct. Conversely, hotels lacking in consistent leadership practices showed weaker integration of both digital systems and Sharia compliance. Transformational leadership is essential in harmonising innovation and Islamic values. The findings of this study provide practical implications for Sharia hotel managers and policymakers to integrate transformational leadership with digital strategies so that technological innovation can enhance competitiveness without compromising adherence to Sharia principles.